Ekonometryczne modelowanie asymetrii reakcji klienta na zmiany cen paliw - Kufel, Tadeusz; Błażejowski, Marcin (Econometric Modeling of Asymmetry in Consumer Reactions to Fuel Price Changes, 2008)
The paper contains discussion about the construction of econometric models for consumer demand based on daily data of transactions in a supermarket. These models take into consideration the asymmetry in consumer reactions to price changes. Coefficients of price elasticity with asymmetry in consumer reaction to increase of price and decrease of price were estimated. There are also several proposals of specification of econometric models for modeling such consumer reactions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 136-143